Impact of Ahmadi Continuing Nursing Model on self-care ability, stoma complications and quality of life of colostomy patients - Huiming Yan; Ying Su; Lina Wang (BMC Gastroenterology, 2024)
Abstract Objective To analyze the effects of Ahmadi Continuing Nursing Model (ACNM) on the self-care ability, stoma complications and life quality in colostomy patients. Methods The clinical data of 120 patients who underwent postoperative colostomy in our hospital from June 2020 to June 2023 were retrospectively analyzed. The patients were divided into control group (n = 60, treated with routine nursing) and observation group (n = 60, treated with the ACNM on the basis of routine nursing) according to different nursing methods. Postoperative recovery of gastrointestinal function, ostomy adaptability, self-care ability, and life quality before and after nursing were compared. The probability of complications before and after nursing was recorded between the two groups. Results The time of first exhaust was 3.65 ± 0.82 d, the time of first meal was 1.83 ± 0.65 d, and the first bowel sound recovery was 1.47 ± 0.53 d in the observation group, which were shorter than those in the control group (4.38 ± 1.20 d, 3.12 ± 1.15 d, 2.39 ± 1.06 d, P < 0.001). After intervention, the positive emotions in the ostomy adaptation score were 32.09 ± 5.03 points, negative emotions were 31.41 ± 5.70 points, social life adaptation were 27.12 ± 4.98 points, and the total score was 90.78 ± 5.98 points in the observation group, which were significantly higher than those in the control group (26.32 ± 4.52 points, 24.25 ± 6.02 points, 20.25 ± 4.02 points, 67.25 ± 6.09 points, P < 0.001). The self-willingness was 34.18 ± 4.02 points, self-care skill was 10.57 ± 2.23 points, self-care knowledge was 18.59 ± 3.10 points, and the total score was 63.18 ± 4.98 points in the observation group, which were significantly higher than those in the control group (25.25 ± 3.08 points, 8.72 ± 2.13 points, 15.26 ± 2.70 points, 45.69 ± 4.09 points, P < 0.001). The physical function was 79.74 ± 2.81 points, psychological function was 76.71 ± 3.05 points, social function was 78.11 ± 3.50 points, and material life status was 60.06 ± 2.98 points in the quality of life in the observation group, which were significantly higher than those in the control group (75.36 ± 2.68 points, 69.72 ± 2.93 points, 72.33 ± 3.42 points, 51.23 ± 3.08 points, P < 0.001). Conclusion ACNM effectively promoted the recovery of gastrointestinal function after surgery in colostomy patients by improving patients’ stoma adaptability, self-care ability and life quality and reducing the occurrence of complications, which was worthy of promotion.